Identifying Outside the Box: An analysis of identification patterns among members of the German minority in Denmark - Zepke, Annika (Academic Quarter | Akademisk kvarter, 2020)
On the basis of six qualitative interviews with members of the German minority in Denmark, the article addresses different ways according to which individuals identify themselves as members of the German minority. The analysis shows that the identification with the minority varies from individual to individual. Identity in the German minority is therefore very multi-layered. Furthermore, the analysis illustrates that members of the minority identify beyond national categories on a rather regional level while comprising both German and Danish linguistic and cultural traits.